ミズホキチ デノ ホウシャ オヨビ ビキショウ ヨウソ カンソク システム - 前, 晋爾; マエ, シンジ; 和田, 誠; ワダ, マコト; 山内, 恭; ヤマノウチ, タカシ; Mae, Shinji; Wada, Makoto; Yamanouchi, Takashi (1981)
P(論文) 1979年から3年計画で南極域観測計画(POLEX-South)が開始された。初年度の1979年には, 第20次南極観測事業の1つとして, みずほ基地に30mの観測塔を建設, 種々の観測センサーを取り付け, 放射および接地気層の精密観測を実施した。放射関係では, 地吹雪が雪面を覆う斜面下降風帯の放射特性を明らかにするため, 雪面上に直達日射計, 4台の全天日射計, 4台の雪面反射計, 上下向き2台の長波長放射計, 熱収支計を設置し, 30m観測塔頂部には全天日射計2台, 雪面反射計2台, 上下向き2台の長波長放射計を設置した。接地層関係では, 30m層内の温度・風分布および雪面下10mまでの雪温分布を主として測定し, 斜面下降風および低気圧接近下での接地気層の微気象的特性を観測することを目的とした。このため雪面上に放射温度計, 飛雪計を設置, 地上30,16,8,4,1,0.5mに温度計, 風速計を, 30,2mに風向計を, さらに雪面および雪面下10,5,3,1,0.5,0.3,0.1mに温度計, 1,0.5,0.1mに熱流板を設置した。これらセンサーからの信号は, みずほ基地内(雪面下3m)に建設したPOLEX棟で処理し記録した。記録方式はテープレコーダーに1分間隔でディジタルに記録する方式と打点式記録計でモニター用に記録する方式をとった。本論文では, これら観測結果の解析に基づいて今後発表される一連の論文の基礎として, 観測のシステムと問題点についてのみ記述することとした。 The Japanese Antarctic Research Expedition operated a three-year project, Polar Experiment South (POLEX-South), from 1979 when the project was limited mainly to the meteorological program, especially the measurements of radiation and vertical profile of temperature and wind in the lowest 30m layer at Mizuho Station (70°42′S, 44°20′E, 2230m above sea level) where katabatic wind blew continuously at a velocity of 12-13 m/s and caused drifting snow. A 30m tower was erected and instrumented in January 1979 and the meteorological program was operational through 1979 and will continue until 1981. The radiation measurements of global shortwave, reflected shortwave, and outgoing and incident longwave were made at the snow surface and at the top of the tower. Direct solar radiation and net radiation were measured only at the snow surface. Temperatures were measured at 15 different levels (7 heights, surface, 7 subsurfaces). Wind velocities and wind directions were measured at 7 levels and 2 levels, respectively. Drifting snow flux, thermal flux in snow, dew point temperature and pressure were also measured. The recording system included a micro-computer, a data logger, transducers, magnetic tape recorders, analog recorders and printing instruments. The measured values were sampled every minute and recorded by magnetic tape recorder and analog recorders. This paper mainly ...